Evaluation of commuter perception and optimization of public transit routes in Hyderabad using TOD applications - Sania Rehman; Mir Aftab Hussain Talpur; Ali Raza Khoso; Imtiaz Ahmed Chandio; Furqan Javed Arain (Mehran University Research Journal of Engineering and Technology)
The accessibility, efficiency, and convenience of public transit in Hyderabad are significantly hindered by inadequate infrastructure, overcrowding, insufficient funding, inconsistent service, traffic congestion, and limited coverage. Urban engineers/urban planners widely recognize the Transit-Oriented Development (TOD) applications as an effective strategy for promoting maintainable urban growth. TOD focuses on situating populations near public transportation hubs to reduce dependence on private vehicles. Hyderabad's public transportation system (buses and trains) currently falls short of meeting commuter needs due to the absence of TOD principles, leading to increased private vehicle usage, traffic congestion, and air pollution. This study aims to evaluate commuter perceptions regarding transportation facilities' availability. It illustrates the service area coverage of the existing public Transit route network based on walkable distances converted to travel times using ArcGIS. Data was collected using an extensive questionnaire survey involving 400 respondents, selected using the Taro technique. Route information was gathered from the Regional Transportation Authority (RTA) and on-site surveys detailing the available public transportation routes. The collected data was analyzed using SPSS software, employing statistical methods such as Chi-Square tests, correlation analysis, normality checks, and ANOVA. The study identified the catchment areas for existing public transportation routes in Hyderabad, emphasizing regions where passengers have easy access to transit in alignment with TOD applications.